A REVIEW ON TEMPLATE SYNTHESIS OF NANOPARTICLE - GHARAT, SAKSHI; GHADGE, AISHWARYA; PHALAK, SWAPNIL D.; BODKE, VISHAL; GAVAND, ADITI; GANVIR, DARSHANA; GAIKWAD, DEEPTI (International Journal of Pharmacy and Pharmaceutical Sciences, 2024)
In recent years, there has been a rise in interest in the development of novel drug delivery systems that utilize nanoparticles. In terms of high stability, high specificity, high drug-carrying capacity, controlled release, the ability to use different routes of administration, and the ability to deliver both hydrophilic and hydrophobic drug molecules, nanoparticles can offer significant advantages over conventional drug delivery. We try to provide a detailed overview of template techniques designed for nanomaterial production. The pores and channels in the nanoporous “template” structures are used to generate the desired nanomaterials in template synthesis. Because this process has advantages over other methods, like allowing precise control over their size, shape, and structure, it is commonly used to generate nanoparticles. The first half of the review provides information on various template preparation processes. Templates are classified as “hard” or “soft” templates. Soft templates are often fluid-like, whereas hard templates are typically solid-state materials with distinct morphology and structure. This study discusses the effect of templates on morphologies and methodology and compares hard and soft templates.